2014
DOI: 10.2478/jas-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Buddleja Thyrsoides for the Control and Prevention of American Foulbrood Disease in Honey Bees

Abstract: a b s t r a c t Paenibacillus larvae is the causative agent of american foulbrood (afb), a severe disease that affects the larvae of the honeybees. the use of plant extracts are considered to be an alternative way of controlling the disease. in this study, the in vitro antimicrobial activity of buddleja thyrsoides lam. against the Paenibacillus species, including P. larvae, was evaluated. in mueller-hinton broth, the minimal inhibitory concentration (miC) was assessed using the microdilution method. all Paenib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…To our knowledge there are not many studies on the effectivity of alcoholic extracts of blueberries, absinthium, oakmoss, oregano, Brewers Gold hops, bay laurel and anise hyssop on bee pathogens [ 33 , 34 , 36 ]. Nevertheless, the results of the current study are in line with results of many other plants extracts, which are used against bee parasites and pathogens (nosemosis, AFB, EFB, chalkbrood), such as: Aristotelia chilensis, Gevuina avellana, Ugni molinae and propolis methanolic extracts [ 40 ] or Buddleja thyrsoides [ 58 ] and Scutia buxifolia [ 59 ]; furthermore, some studies use Humulus lupulus and Myrtus communis [ 60 ], Origanum vulgare and Rosmarinus officinalis [ 61 ] or Laurus nobilis [ 12 , 33 , 34 ]. However, others showed that bay laurel oil and phenolic extracts of berries had very low or no activity on Gram-positive bacteria [ 11 ].…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge there are not many studies on the effectivity of alcoholic extracts of blueberries, absinthium, oakmoss, oregano, Brewers Gold hops, bay laurel and anise hyssop on bee pathogens [ 33 , 34 , 36 ]. Nevertheless, the results of the current study are in line with results of many other plants extracts, which are used against bee parasites and pathogens (nosemosis, AFB, EFB, chalkbrood), such as: Aristotelia chilensis, Gevuina avellana, Ugni molinae and propolis methanolic extracts [ 40 ] or Buddleja thyrsoides [ 58 ] and Scutia buxifolia [ 59 ]; furthermore, some studies use Humulus lupulus and Myrtus communis [ 60 ], Origanum vulgare and Rosmarinus officinalis [ 61 ] or Laurus nobilis [ 12 , 33 , 34 ]. However, others showed that bay laurel oil and phenolic extracts of berries had very low or no activity on Gram-positive bacteria [ 11 ].…”
Section: Discussionsupporting
confidence: 85%
“…Plant extracts such as Buddleja thyrsoides (Boligon et al . ), Humulus lupulus L., Myrtus communis L. (Flesar et al . ), Scutia buxifolia (Boligon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activity of other plant species against P. larvae has been previously studied. Plant extracts such as Buddleja thyrsoides (Boligon et al 2014), Humulus lupulus L., Myrtus communis L. (Flesar et al 2010), Scutia buxifolia (Boligon et al 2013) and Laurus nobilis (Damiani et al 2014) showed inhibitory activity against P. larvae with MIC values of 7Á51-16Á90 mg ml À1 , 2-4 lg ml À1 , 2-8 lg ml À1 , 50 mg ml À1 and 208-416 lg ml À1 respectively. In addition, propolis (plant resins collected by bees) has shown efficacy in inhibiting American Foulbrood (Antunez et al 2008;Bastos et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…After that, the remaining aqueous extract was partitioned with dichloromethane (DCM), ethyl acetate (EA) and n-butanol (NB), successively. 10…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%
“…8,9 Their chemical structure is characterized by having a hydroxyl attached directly to an aromatic hydrocarbon group, and exhibit different biological effects, such as antitumor, antioxidant, anti-inflammatory, antiviral and antimicrobial activities. [10][11][12][13] Therefore, the phenyl compounds could be used as an alternative, to increase our therapeutic arsenal, because the disorderly use of antimicrobial drugs is contributing to the growth of micro-organisms that are resistant to treatments; namely, these strains are able to multiply in the presence of antimicrobial concentrations higher than the doses recommended for the treatment of the patient. [14][15][16] After the discovery of the first antimicrobial drugs, it was evident that bacteria possessed resistance mechanisms; however, this scenario was livened up with the frequent introduction of new antibiotics.…”
Section: Introductionmentioning
confidence: 99%